Architectural graphic standards for architects, engineers, decorators, builders, and draftsmen - Ramsey, Charles G. 1884-1963. (John Wiley and Sons, 1998)
Orientation, retaining walls, exterior steps, brick paving, masonry floors and paving, piles, footings and foundations, waterproofing, waterproofing-plaster coat, structural steel, reinfocing bars, brickwork, brick walls, fireplaces...